Evaluation of Effects of Different Core & Veneer Thickness Combination on Translucency of Two All Ceramic System: An in Vitro Study" - BHUMIKA SANGTANI; KAVITA MARU; MANISH SANGTANI; ARCHITA GANGWAL (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: The study aimed to evaluate the effect of change in thickness of core or veneer ceramic on translucency of two types of Lithium Di Silicate Glass Ceramic IPS e-max PRESS and IPS e-max CAD. Methods: A total of 56 disks (IPS e.max PRESS, IPS e.max CAD; Ivoclar Vivadent), 15 mm in diameter with different thicknesses (0.80 mm, 1.00 mm), were fabricated as core materials with the lost wax and heat-press techniques, according to the manufacturer’s recommendations. They were divided into groups (n=7), the size of which was determined by power analysis (Δ=0.2; power=0.80; α=0.05). Each core material was veneered with its compatible veneer ceramic (IPS e.max PRESS, IPS e.max CAD. All surfaces were measured by profilometry to ensure consistency within the groups. A glass disk (1.5 mm) positive control (group P) and a metal core (1.5 mm) negative control (group N) were prepared. The translucency parameter (TP) values were calculated using spectrophotometry to calculate the color differences of the specimens over black and white backgrounds. Results: IPS e.max PRESS and IPS e.max CAD depicted decreasing order or mean % transmittance as 0.15477 for IPS e.max PRESS (0.5+0.5), 0.14431 IPS e.max PRESS (0.8+0.2), 0.06671 IPS e.max CAD (0.5+0.5), 0.06297 IPS e.max CAD (0.8+0.2). The difference between these groups was found to be statistically significant (p<0.05). However, not significant difference found between Group 1 IPS e.max PRESS (0.8+02)-Group2 IPS e.max PRESS (0.5+0.5) and Group5 IPS e.max CAD (0.8+0.2)-Group6 IPS e.max CAD (0.5+0.5) pairs (p>0.05). One-way analysis of variance found significant differences among the TP values of the ceramic groups (p<0.05). Conclusion: When overall thickness was increased to 1.5 mm, keeping similar veneer at 0.5 mm IPS e-max CAD exhibited better esthetic outcome than IPS e-max PRESS. Interaction of core and veneer are different with different ceramic systems at different thicknesses. Most appropriate ceramic material can be decided based only on specific clinical situation being faced.